The blast from the past - Score, Lucy (Riley Thorn, 2024)
"#1 New York Times bestselling author Lucy Score's suspenseful reluctant psychic Riley Thorn series features hapless Riley and her hot tattooed PI boyfriend Nick Santiago who's determined to keep her safe at all costs. They're are all moved in to their new fixer-upper, finally have their own place, and no new dead bodies for some time. But then a woman from Nick's past shows up and throws a wrench into everything"--